2017
DOI: 10.1177/1535370217723578
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia training in prediabetes patients: Beneficial effects on glucose homeostasis, hypoxia tolerance and gene expression

Abstract: The present study investigated the beneficial effects of intermittent hypoxia training (IHT) in humans under prediabetic conditions. We found that three-week moderate IHT induced higher HIF-1a mRNA expressions as well as its target genes, which were positively correlated with higher tolerance to acute hypoxia and better glucose homeostasis in both middle-aged healthy and prediabetic subjects. This small clinical trial has provided new data suggesting a potential utility of IHT for management of prediabetes pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 75 publications
0
43
0
Order By: Relevance
“…Intermittent exposure to both normobaric and hypobaric hypoxia has been related to some protective effects (Cai et al, 2003 ; Costa et al, 2013 ) and beneficial outcomes in several pathological conditions, especially in those related to metabolic syndrome (Marquez et al, 2013 ; Leone and Lalande, 2017 ; Serebrovska et al, 2017 ). The possible role of intermittent hypoxia on body weight control has also attracted considerable attention.…”
Section: Biological Effects Of Intermittent Hypoxia Exposurementioning
confidence: 99%
“…Intermittent exposure to both normobaric and hypobaric hypoxia has been related to some protective effects (Cai et al, 2003 ; Costa et al, 2013 ) and beneficial outcomes in several pathological conditions, especially in those related to metabolic syndrome (Marquez et al, 2013 ; Leone and Lalande, 2017 ; Serebrovska et al, 2017 ). The possible role of intermittent hypoxia on body weight control has also attracted considerable attention.…”
Section: Biological Effects Of Intermittent Hypoxia Exposurementioning
confidence: 99%
“…From the theoretical point of view, exercise combined with hypoxic exposure could be much helpful to reduce more blood lipids. For prediabetes patients, it has also been repeated breath intermittent hypoxia (12% O 2 ) could decrease serum glucose, cholesterol, and LDL [52,53]. Applying hypoxic training to improve blood lipids in individuals with obesity is one of the main expectations.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that a few weeks of exercise in moderate hypoxia resulted in more significant weight loss in individuals with obesity, as compared to exercising with the same or higher intensities under normoxia [ 10 12 ]. However, there have been only a small number of reports on the effects of repeated exposure to IHI for several weeks, without a combination of other types of intervention, on fasting blood glucose (FBG) and insulin (FBI) [ 7 , 13 ], with inconsistent outcomes. For example, Serebrovska et al [ 7 ] reported that in older adults with pre-diabetes, nine sessions of IHI in three weeks with the fraction of oxygen in the inspired air (FiO 2 ) of 0.12, did not result in a significant decrease in FBG at the end of the intervention period, but a significant decrease was found one month post the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been only a small number of reports on the effects of repeated exposure to IHI for several weeks, without a combination of other types of intervention, on fasting blood glucose (FBG) and insulin (FBI) [ 7 , 13 ], with inconsistent outcomes. For example, Serebrovska et al [ 7 ] reported that in older adults with pre-diabetes, nine sessions of IHI in three weeks with the fraction of oxygen in the inspired air (FiO 2 ) of 0.12, did not result in a significant decrease in FBG at the end of the intervention period, but a significant decrease was found one month post the intervention. Schreuder et al [ 13 ] reported that an eight-week exercise-program significantly improved physical fitness of type 2 diabetes patients, but the addition of hypoxia (0.165 FiO 2 ) did not potentiate the effects of the exercise on fitness, vascular function and glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%